Neutron and X-ray diffraction and empirical potential structure refinement modelling of magnesium stabilised amorphous calcium carbonate - Rodriguez-Blanco, Juan (My University, 2014)
Amorphous calcium carbonate (ACC) plays a key role in biomineralisation processes in sea organisms. Neutron and X-ray diffraction have been performed for a sample of magnesium-stabilised ACC, which was prepared with a Mg:Ca ratio of 0.05:1 and 0.25 H2O molecules per molecule of CO3. The empirical potential structure refinement method has been used to make a model of magnesium-stabilised ACC and the results revealed a fair agreement with the experimental diffraction data. The model has well-defined CO3 and H2O molecules. The average coordination number of Ca is 7.4 and is composed of 6.8 oxygen atoms from CO3 molecules and 0.6 oxygen atoms from H2O molecules. The average CaO bond length is 2.40 Å. The distribution of Ca in the model is homogeneous with a uniformly distributed Ca-rich network and no evidence of the Ca-poor channels as previously reported for a reverse Monte Carlo model of ACC.
PUBLISHED
Keywords: Amorphous calcium carbonate (ACC); EPSR modelling; Neutron diffraction; X-ray diffraction; Nanoscience & Materials